(untitled) (Arquivos Catarinenses de Medicina, 2025)
Introduction: The objective of the study was to analyze the growth achieved and its relation with nutritional status among school adolescents attending public schools in capital of the South of Brazil. Method: cross-sectional, analytical study with a convenience sample of 7,225 schoolchildren aged 10 to 16 years of age from public schools, selected from the anthropometric evaluation (weight, height, and Body Mass Index - BMI) of the Health Program of School. Classification according to groups of height for age: Group of Heights (GA) with z Height (zE) for Age greater than 1, Medium Group (GM) zE 1 and less 1 and, Group of Low (GB) and zE below of less than 1, for both sexes. BMI z score values ​​(z IMC) of GA and GB were compared and z IMC correlation and sex were found. The Kruskal-Wallis test and Mann-Whitney test and Spearman's correlation coefficient were used. The study was approved by the Ethics Committee on Research in Human Beings. Results: There was statistically significant difference between BMI of Male Altos (BMI) versus BMI of Male Low (MB) (p <0.0001) and between BMI Female High (BMI) versus BMI Female Low, (p <0.0001) statistically significant BMI MA versus BMI FA (p = 0.0005). There is a correlation between z IMC and zE of male GA (p = 0.0023) and z IMC with male GB zE (p <0.001). Conclusion: fast growth is associated with body weight gain and the tendency of overweight and obesity, stressing the importance of monitoring both height and body mass in adolescence.